Pengaruh Kualitas Pelayanan, Harga Serta Lokasi pada Kepuasan Pelanggan: Studi Pada Lbb Ganesha Operation Kota Pacitan - Handayani, Rini; Sugiyanto, Aan (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This research focuses on efforts to increase customer satisfaction at tutoring institutions, especially at LBB Ganesha Operation Pacitan City. The focus is to analyze the impact of service quality, price, also location on student satisfaction. The research method used was a quantitative approach, with 80 LBB Ganesha Operation students in Pacitan City as the sample selected using a purposive sampling method. Analysis was done using multiple linear regression techniques with SPSS 22 for Windows. The test results show service quality influences 0.315, price -0.111, also location 0.444. The F test value shows these three variables jointly influence student satisfaction (F count 67.532 > F table 2.72, with a significance level of 0.000 < 0.05). The t-test shows service quality also location have a significant partial influence on customer satisfaction (t count 3.551 also 4.819 respectively > t table 1.990). In contrast, price does not have a significant partial influence (t count -1.812 < t table 1.990). The coefficient of determination shows 71.6% of the variation in customer satisfaction can be explained by service quality, price, also location, while the remaining 28.4% is influenced by other factors. It was concluded service quality also location had a positive also significant influence on student satisfaction at LBB Ganesha Operation Pacitan City, but the price did not have a significant influence.